2017
DOI: 10.31298/sl.141.9-10.6
|View full text |Cite
|
Sign up to set email alerts
|

First record of alien species Chymomyza amoena [Diptera

Abstract: Strana vrsta Chymomyza amoena (Loew 1862) zabilježena je prvi puta u Hrvatskoj. Ova fitofagna vrsta octene muhe porijeklom iz Sjeverne Amerike otkrivena je u Europi 1975. godine na području nekadašnje Čehoslovačke, a već 1980. godine zabilježena u dvije nama susjedne države (Mađarskoj i Srbiji). Smatra se da se C. amoena proširila uvozom jabuke iz Amerike u Europu, a velik broj dostupnih biljaka domaćina (domaće jabuke, engleski hrast te europski kesten) zaslužan je za široku rasprostranjenost vrste u Europi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The presence of Chymomyza amoena has been confirmed in the northern part of Croatia [ 30 ], and this study has revealed its presence at six new localities in the Istria region. The collecting localities are surrounded by Mediterranean forests and extensive production of grapes, figs, and sweet cherries.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The presence of Chymomyza amoena has been confirmed in the northern part of Croatia [ 30 ], and this study has revealed its presence at six new localities in the Istria region. The collecting localities are surrounded by Mediterranean forests and extensive production of grapes, figs, and sweet cherries.…”
Section: Discussionsupporting
confidence: 52%
“…Drosophila suzukii (Matsumura, 1931) was the most abundant invasive alien species found at every sampling site. Moreover, we found a total of 34 specimens of Chymomyza amoena (Loew 1862); this species was previously confirmed only twice in Croatia [ 30 , 47 ]. Callopistromyia annulipes was also found in fourteen locations with 265 specimens, representing the second record in Croatia.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It is not considered a true pest (Band & Band, 1980;Pajač Živkovi c et al, 2017) at present and has received much less research attention than D. suzukii. Native to North America, it has become widely established in Europe since its first detection in 1975 in Czechia (Band et al, 2005;de Jong & van Zuijlen, 2003;Pajač Živkovi c et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, communities of frugivorous species have been impacted by invasive exotic species. For instance, in Europe, the invasive members of the Drosophilidae family, Drosophila suzukii Matsumara and Chymomyza amoena Loew, are highly polyphagous and could profoundly alter the structure of Drosophilidae communities developing in fresh and decaying fruit by using the same resources as native species (Band et al, 2005; Pajač Živković et al, 2017; Poyet et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%